2015
DOI: 10.1007/s11705-015-1525-3
|View full text |Cite
|
Sign up to set email alerts
|

High production of butyric acid by Clostridium tyrobutyricum mutant

Abstract: The objective of this study was to improve the production of butyric acid by process optimization using the metabolically engineered mutant of Clostridium tyrobutyricum (PAK-Em). First, the free-cell fermentation at pH 6.0 produced butyric acid with concentration of 38.44 g/L and yield of 0.42 g/g. Second, the immobilizedcell fermentations using fibrous-bed bioreactor (FBB) were run at pHs of 5.0, 5.5, 6.0, 6.5 and 7.0 to optimize fermentation process and improve the butyric acid production. It was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Nevertheless, the final product purity (butyric acid/total acids) obtained from these fermentations was ∼0.99, which was a dramatic improvement over the control (0.79 for BV 0 at pH 6.0). Overall, the best butyrate production, including higher final butyrate concentration, yield and productivity, was obtained at pH 6.5, which could be attributed to the alleviated product inhibition caused by butyric acid at the higher pH value (Ma et al, 2015; Michel‐Savin et al, 1990; Zhu & Yang, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the final product purity (butyric acid/total acids) obtained from these fermentations was ∼0.99, which was a dramatic improvement over the control (0.79 for BV 0 at pH 6.0). Overall, the best butyrate production, including higher final butyrate concentration, yield and productivity, was obtained at pH 6.5, which could be attributed to the alleviated product inhibition caused by butyric acid at the higher pH value (Ma et al, 2015; Michel‐Savin et al, 1990; Zhu & Yang, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The genus Clostridium consists of approximately 180 species, a few of which are pathogenic, producing very harmful toxins. However, Clostridium species are also used in biotechnological and therapeutic applications [ 73 , 74 , 75 , 76 , 77 ]. Many clostridia have been reported to produce butyric acid—a short-chain fatty acid (SCFA)—as a major fermentation product.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent butyrate fermentation using C. tyrobutyricum showed that the fermentation pH significantly affected the production of butyrate and cell growth [ 33 ]. Specifically, the immobilized-cell fermentations at pH 6.0, 6.5 and 7.0 produced butyrate with concentrations of 50.11 g/L, 63.02 g/L and 61.01 g/L.…”
Section: Discussionmentioning
confidence: 99%
“…To effectively integrate cell engineering and process engineering, metabolomics should be developed and applied to C. tyrobutyricum . Metabolic flux analysis modeling is also an effective tool to guide the design of metabolic engineering [ 33 , 34 ]. In addition, the medium components can be rationally designed to assist in butanol production post cell engineering.…”
Section: Discussionmentioning
confidence: 99%